Evaluation of nutritional quality and health benefits of milky mushroom (Calocybe indica P&C) - Anju R P (Department of Home Science, College of Agriculture, 2013)
“Evaluation of nutritional quality and health benefits of milky mushroom” (Calocybe indica P&C)” was an in-depth study undertaken to determine the nutritional quality, nutrient loss during processing and also to investigate the health impact of the mushroom supplement on the blood profile of the subjects with specific disease condition.